2022
DOI: 10.3390/ijerph19127412
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sport Practice and Body Weight on Physical Fitness in Schoolchildren Living in the Campania Region

Abstract: Background: Physical fitness (PF) levels correlate with health hallmarks at all ages. In this study, w aimed to determine the PF level of schoolchildren from the Campania Region (Italy) through health-related PF (HRPF) components, taking into account body weight and sport practice (SP). Methods: PF level was determined in 565 schoolchildren aged 10–13 (11.7 ± 1.0 yrs; m: 353, f: 212) using some of the Eurofit battery tests. Results: 77% children practiced sport, boys more than girls (86% vs. 63%, respectively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
1
3
0
1
Order By: Relevance
“…Also, in a study by Gea-García et al (2020) boys scored higher on tests similar to those presented in this study [14]. The opposite was observed in the study by Mancini et al (2022) conducted on children aged 10-13, which reported no differences in the speed test between physically active boys and those not undertaking additional PA [57]. However, it was a pilot study and long-term outcomes were not monitored.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Also, in a study by Gea-García et al (2020) boys scored higher on tests similar to those presented in this study [14]. The opposite was observed in the study by Mancini et al (2022) conducted on children aged 10-13, which reported no differences in the speed test between physically active boys and those not undertaking additional PA [57]. However, it was a pilot study and long-term outcomes were not monitored.…”
Section: Discussionsupporting
confidence: 65%
“…. Studies byZhang et al (2021) [66] andMancini et al (2022) [57] also indicated better scores in the core strength test in girls, as already discussed above.Analysis of the fitness test results in the present study showed that children performed best in the agility test, i.e., the 10 × 5 m shuttle run. On average, children with increased PA at school achieved more favorable scores in the agility test than those of standard PA (21.56 s and 22.07 s; respectively).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…El evaluador entregó las instrucciones para realizar el inicio del salto y el participante buscó alcanzar la máxima distancia horizontal. Se realizaron 2 intentos y se registró el mejor de ambos, evaluando el lugar del apoyo del cuerpo que se encuentre más cerca de la línea de salida inicial (Mancini et al, 2022).…”
Section: Mediciones De La Condición Físicaunclassified